Nucleophilic 5-endo-trig Cyclization of 3,3-Difluoroallylic Metal Enolates and Enamides: Facile Synthesis of Ring-Fluorinated Dihydroheteroles - Fujita, Takeshi; Ikeda, Masahiro; Hattori, Masahiro; Sakoda, Kotaro; Ichikawa, Junji (Synthesis, 2014)
Metal enolates and enamides bearing difluoroallylic moieties underwent nucleophilic 5-endo-trig cyclization, a process considered to be disfavored according to Baldwin’s rules. Whereas no C-cyclization was observed in these reactions, O- and N-cyclization proceeded exclusively to afford 5-fluorinated 2-alkylidene-2,3-dihydrofurans and -2,3-dihydropyrroles, respectively.
Keywords: cyclizations; fluorine; heterocycles; furans; pyrroles; ring closure